Analisis Struktur Modal Perusahaan Rokok yang Terdaftar di Bursa Efek Indonesia - Wiguna, Ketut Pradnyana; Yasa, Gerianta Wirawan (E-Jurnal Akuntansi; Vol 33 No 6 (2023), 2023)
The research aims to analyze the capital structure of the cigarette business listed on the IDX for 2016-2021 which is thought to be influenced by asset structure, liquidity and profitability. The population used is the cigarette business listed on the IDX for the 2016-2021 period with a sample determined using certain criteria (purposive sampling method) and obtained 5 issuers as the sample. Data analysis used multiple linear regression analysis techniques. The results of the study prove that asset structure has a positive impact, while liquidity and profitability have a negative impact on the capital structure of cigarette companies. This condition proves that a business when determining its capital structure pays attention to the profit it can generate, the ownership of fixed assets that can be used as collateral for debt, and the smoothness of paying short-term debt. Keywords:Capital Structure; Asset Structure; Liquidity; Profitability